Establishment and characterization of a novel MYC/BCL2 "double-hit" diffuse large B cell lymphoma cell line, RC. Issue 1 (December 2015) - Pham, Lan; Lu, Gary; Tamayo, Archito; Chen, Juan; Challagundla, Pramoda; Jorgensen, Jeffrey; Medeiros, L.; Ford, Richard
Abstract Background Diffuse large B cell lymphoma (DLBCL) is the most common type of lymphoid malignancy worldwide. Approximately 5 % of cases of DLBCL are so-called double-hit lymphomas (DHL), defined by a chromosomal translocation or rearrangement involvingMYC /8q24.2 in combination with another recurrent breakpoint, usuallyBCL2 /18q21.3. Patients withMYC/BCL2 DHL are resistant to standard front-line therapy, and currently, there is no consensus for a therapeutic strategy to treat these patients. Lack of clinically relevant or validated human experimental DHL models of any type that would improve our understanding of the biologic basis ofMYC/BCL2 DHL pathophysiology continues to hamper identification of valid therapeutic targets. We describe a uniqueMYC/BCL2 DHL cell line with morphologic features of DLBCL that we have established, designated as RC. Methods We used tissue culture techniques to establish the RC cell line from primary DLBCL cells. We also utilized molecular and cellular biological techniques including flow cytometry, polymerase chain reaction (PCR), DNA fingerprinting, reverse-phase protein array, conventional cytogenetics, and fluorescence in situ hybridization (FISH) analysis to characterize the RC cell line. NSG-severe combined immunodeficiency (SCID) mice were utilized as a model for xeno-transplantation of RC cells. Results RC cells had the following immunophenotype: positive for CD10, CD19, CD20, CD22, CD38, CD43, CD44, and CD79b and negative for CD3, CD4, CD5, CD8, CD11c, CD14, CD30, CD56, and CD200, which was identical to the primary tumor cells. Conventional cytogenetic analysis showed a t(2;8)(p12;q24.2) and t(14;18)(q32;q21.3), corresponding toMYC andBCL2 gene rearrangements, respectively. DNA fingerprinting authenticated the RC cell line to be of the same clone as the primary tumor cells. In addition, RC cells were established in SCID mice as an in vivo model for translational therapeutics studies. Proteomic analysis showed activation of the mTOR signaling pathway in RC cells that can be targeted with an mTOR inhibitor. Conclusion The data presented confirm the validity of the RC cell line as a representative model ofMYC/BCL2 DHL that will be useful for both in vitro and in vivo studies of DHL pathogenesis and therapeutics.